2021
DOI: 10.3390/v13061030
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ampeloviruses Infecting Cassava in Central Africa and the South-West Indian Ocean Islands

Abstract: Cassava is one of the most important staple crops in Africa and its production is seriously damaged by viral diseases. In this study, we identify for the first time and characterize the genome organization of novel ampeloviruses infecting cassava plants in diverse geographical locations using three high-throughput sequencing protocols [Virion-Associated Nucleotide Acid (VANA), dsRNA and total RNA], and we provide a first analysis of the diversity of these agents and of the evolutionary forces acting on them. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Similarly, papaya mealybugs (Paracoccus marginatus Williams) has been reported along the coastal belts of Kenya especially in Kwale, Kilifi, Mombasa, and Taita-Taveta counties on papaya, cassava, chili pepper, amaranth, coconut, and other fruits, ornamental plants and weeds (Macharia et al, 2017). Mealy bugs have been reported as vectors of many species of viruses (Selvarajan et al, 2016) including the recently identified novel amplelovirus infecting cassava in Central Africa and South West Ocean islands (Kwibuka et al, 2021). Future studies therefore recommend investigative studies on the possible role played by the mealybug species observed on cassava in the coastal region of Kenya in the spread of CBSD during their feeding patterns on cassava.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, papaya mealybugs (Paracoccus marginatus Williams) has been reported along the coastal belts of Kenya especially in Kwale, Kilifi, Mombasa, and Taita-Taveta counties on papaya, cassava, chili pepper, amaranth, coconut, and other fruits, ornamental plants and weeds (Macharia et al, 2017). Mealy bugs have been reported as vectors of many species of viruses (Selvarajan et al, 2016) including the recently identified novel amplelovirus infecting cassava in Central Africa and South West Ocean islands (Kwibuka et al, 2021). Future studies therefore recommend investigative studies on the possible role played by the mealybug species observed on cassava in the coastal region of Kenya in the spread of CBSD during their feeding patterns on cassava.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, viruses from the genus Tenuivirus have almost complementary 3′ and 5′ genome ends ( Gaafar et al, 2021 ), which can provide an indication on genome completeness. Similarly, if the novel genome contains a 3′ poly-A tail or the assembled genome length is very similar to that of closely related viruses, it provides an indication that the UTRs are likely complete or only missing a few nucleotides ( Kwibuka et al, 2021 ). However, if an incomplete genome assembly is obtained, it is a good practice to carry out additional analyses to complete the genome, such as iterative mapping of unassembled reads ( Olmedo-Velarde et al, 2022 ).…”
Section: Detection Test Confirmation Of Detection and Genome Sequencementioning
confidence: 99%
“…Collecting this information at the time of sampling can facilitate and minimize efforts later on. Additionally, the documentation could include the economic importance and geographical distribution of the crop species affected, globally or domestically ( Kwibuka et al, 2021 ). Optionally, plants that are taxonomically related to the infected hosts, including other crops and wild plants that could potentially be threatened by the virus or be a reservoir or alternate host, could also be documented.…”
Section: Contextual Information Gathering and Notification To Stakeho...mentioning
confidence: 99%
See 1 more Smart Citation
“…This technique employs the use of RNA interference (RNAi), a natural antivirus defense mechanism present in the host cell, to generate small RNAs that are 21-24 nt long for the analysis of the viral population present in a tested plant sample [10]. The technique has become an important tool and has been used widely in the diagnosis, identification, and characterization of viruses in recent years [5,[11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%